Liposomes are Poorly Absorbed via Lung Lymph After Inhaled Administration in Sheep - Ibrahim, Jibriil P; Haque, Shadabul; Bischof, Robert J; Whittaker, Andrew K; Whittaker, Michael R; Kaminskas, Lisa M (Frontiers in Pharmacology, 2022)
Enhancing the delivery of therapeutics to the lung lymph, including drugs, transfection agents and vaccines, has the potential to improve the treatment and prevention of a range of lung-related illnesses. One way lymphatic delivery can be optimised is via nanomaterial-based carriers, such as liposomes. After inhaled delivery however, there is conflicting information regarding whether nanomaterials can sufficiently access the lung lymphatics to impart therapeutic benefit, largely due to a lack of reliable quantitative pharmacokinetic data. We aimed to quantitatively evaluate the pulmonary lymphatic pharmacokinetics of a model nanomaterial-based drug delivery system (3H-labelled HSPC liposomes) in caudal mediastinal lymph duct cannulated sheep after nebulised administration to the lungs. While nanomaterials administered to the lungs may access the lymphatics via direct absorption from the airways or after initial uptake by alveolar macrophages, only 0.3% and 0.001% of the 3H-lipid dose was recovered in lung lymph fluid and lymph cell pellets (containing immune cells) respectively over 5 days. This suggests limited lymphatic access of liposomes, despite apparent pulmonary bioavailability of the 3H-lipid being approximately 17%, likely a result of absorption of liberated 3H-lipid after breakdown of the liposome in the presence of lung surfactant. Similarly, biodistribution of 3H in the mediastinal lymph node was insignificant after 5 days. These data suggest that liposomes, that are normally absorbed via the lymphatics after interstitial administration, do not access the lung lymphatics after inhaled administration. Alternate approaches to maximise the lung lymphatic delivery of drugs and other therapeutics need to be identified.